2014
DOI: 10.1530/joe-14-0203
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin regulation and role of ovarian osteopontin in the periovulatory period

Abstract: Osteopontin (OPN), a secreted glycoprotein, has multiple physiological functions. This study investigated the regulation and roles of OPN in the mouse ovary during the periovulatory stages. Immature female mice were treated with pregnant mare serum gonadotropin (PMSG) and human chorionic gonadotropin (hCG) to simulate follicle maturation and ovulation. In situ hybridization and real-time RT-PCR were performed to assess expression of Opn in the periovulatory ovary. Granulosa cells (GCs) from PMSGprimed immature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
2
10
0
3
Order By: Relevance
“…Adipose tissue dysfunction may also impact the pathophysiology of PCOS through its influence on metabolism and reproductive systems (6). In the present study, circulating OPN levels were significantly elevated in women with PCOS, and also overweight/obese women had significantly higher circulating OPN levels than lean (22) recently reported that OPN might be involved in the regulation of follicular growth and ovulation. They showed that OPN expression increased in mouse ovarian granulosa cells in response to gonadotropin.…”
Section: European Journal Of Endocrinologysupporting
confidence: 54%
See 1 more Smart Citation
“…Adipose tissue dysfunction may also impact the pathophysiology of PCOS through its influence on metabolism and reproductive systems (6). In the present study, circulating OPN levels were significantly elevated in women with PCOS, and also overweight/obese women had significantly higher circulating OPN levels than lean (22) recently reported that OPN might be involved in the regulation of follicular growth and ovulation. They showed that OPN expression increased in mouse ovarian granulosa cells in response to gonadotropin.…”
Section: European Journal Of Endocrinologysupporting
confidence: 54%
“…They also observed that circulating OPN levels significantly increased following gonadotropin administration. They showed that OPN increases progesterone synthesis and expression of vascular endothelial growth factor (VEGF) in the early luteal phase (22). In addition, it has been previously demonstrated that circulating levels of certain adipokines show variations during the menstrual cycle (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Васкуляризация яичника в репродуктивном периоде онтогенеза регулируется и такими фак-торами, как остеопонтин, тромбоспондин-1, дельта-подобный лиганд 4, прокинетицин-1 и простагландин Е2 [11,21]. Все ýти факторы по-разному способствуют выживанию и функ-ционированию овариального резерва и профи-лактируют аномальный ангиогенез [11].…”
Section: производный фактор пигментного эпителияunclassified
“…Ангиогенная активность находится под контро-лем основных ростовых факторов: сосудисто-ýн-дотелиального фактора роста, фактора роста фибробластов, ýпидермального фактора роста, фактора роста тромбоцитов, инсулино-подобно-го фактора роста-1, а также цитокинов (таких, как тумор-некротический фактор, интерлейки-ны, компоненты ýкстрацеллюлярного матрикса (ламинин, фибронектин) и их рецепторы (ин-тегрины), матричные металлопротеиназы и их тканевые ингибиторы и регуляторы, протеазы (плазминоген, активаторы урокиназы и уроки-назы тканевого типа), а также гипоксия, гипо-гликемия и стресс [1,8,10,18,19,20,21,22,23,24,25]. Следовательно, процессы ангиогенеза контролируются индукторами и ингибиторами васкуляризации [8,26,27].…”
unclassified
“…Interestingly, Kuwabara et al, [10] reported that there is a link between OPN and ovarian function, as its expression in mouse ovaries and circulating levels were increased after gonadotropin administration.…”
Section: Introductionmentioning
confidence: 99%